2014
DOI: 10.1038/hdy.2014.2
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence variation of wild barley Hordeum spontaneum (L.) across environmental gradients in Israel

Abstract: Wild barley Hordeum spontaneum (L.) shows a wide geographic distribution and ecological diversity. A key question concerns the spatial scale at which genetic differentiation occurs and to what extent it is driven by natural selection. The Levant region exhibits a strong ecological gradient along the North-South axis, with numerous small canyons in an East-West direction and with small-scale environmental gradients on the opposing North-and South-facing slopes. We sequenced 34 short genomic regions in 54 access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…Although we find no evidence that microsatellites contribute to local adaptations in Evolution Canyon, mobile elements emerge as potential surrogates of adaptive divergence along the sharp microclimate gradient. A similar conclusion has been reached in a study of wild barley (Hordeum spontaneum) from Evolution Canyon (49,50), showing that more BARE-1 retrotransposon copies and proportionally fewer solo LTRs were found in the upper, drier sites of the canyon, particularly at the top of the SFS, than at lower sites. Interestingly, the pattern seems to be roughly opposite to D. melanogaster whose NFS genomes carry a heavier TE load.…”
Section: Resultssupporting
confidence: 56%
“…Although we find no evidence that microsatellites contribute to local adaptations in Evolution Canyon, mobile elements emerge as potential surrogates of adaptive divergence along the sharp microclimate gradient. A similar conclusion has been reached in a study of wild barley (Hordeum spontaneum) from Evolution Canyon (49,50), showing that more BARE-1 retrotransposon copies and proportionally fewer solo LTRs were found in the upper, drier sites of the canyon, particularly at the top of the SFS, than at lower sites. Interestingly, the pattern seems to be roughly opposite to D. melanogaster whose NFS genomes carry a heavier TE load.…”
Section: Resultssupporting
confidence: 56%
“…We identified over one thousand SNPs in wild barley, resulting in 4.4 SNPs per kb at high coverage. This is similar to a recent survey of wild barley collected across Israel (one SNP per 239 bp, θ w =0.00418) [ 10 ]. We also identified over one thousand SNPs by mapping against the cultivated barley sequences (Hv.…”
Section: Discussionsupporting
confidence: 88%
“…Throughout its geographical distribution, wild barley is exposed to multiple environmental stresses such as drought, high temperatures, and high soil salinity. The correlation of genetic and environmental variation within its distribution range suggests the action of local adaptation along macro- and micro-environmental gradients [ 8 10 ]. It is therefore an excellent model system for studying plant adaptation and holds a high potential as a genetic resource for the breeding of stress tolerant varieties of cultivated barley [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The level of genetic variation in H. spontaneum has been studied and estimated using phenotypic characters, isozymes and different PCR-based molecular markers (Turpeinen et al 2003;Jana and Pietrzak 1988;Dreiseitl and Dinoor 2004;Jaradat 1991;Baum et al 2004;and Bedada et al 2014). These studies concluded that the genetic variation in wild barley is substantial.…”
mentioning
confidence: 98%